2020
DOI: 10.1177/1758573220964807
|View full text |Cite
|
Sign up to set email alerts
|

The use of Tightrope device as the sole method of fixation in treating lateral end clavicle fractures

Abstract: Background Lateral end clavicle fractures can be challenging due to the small and often comminuted lateral fragment, problems with union and stability and implant morbidity. We retrospectively reviewed outcomes of Tightrope device in isolation to treat lateral end clavicle fractures. Methods Subjective and objective measures were assessed for 29 patients. The subjective comprised of functional clinical scores: Oxford shoulder score and EuroQoL5D. The objective measures were maintenance of fracture reduction, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(28 citation statements)
references
References 24 publications
0
17
0
11
Order By: Relevance
“…Moreover, two patients had mild forward flexion limitation, and another two patients had mild discomfort when performing demanding activities. Al-Tawil et al 1 have reported at a mean follow-up of 21 months that standalone TightRope device fixation achieved high union rates (22 out of 23 patients). Three complications were encountered in this series consisting of shoulder stiffness, prominence of the TightRope implant, and coracoid button migration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, two patients had mild forward flexion limitation, and another two patients had mild discomfort when performing demanding activities. Al-Tawil et al 1 have reported at a mean follow-up of 21 months that standalone TightRope device fixation achieved high union rates (22 out of 23 patients). Three complications were encountered in this series consisting of shoulder stiffness, prominence of the TightRope implant, and coracoid button migration.…”
Section: Discussionmentioning
confidence: 99%
“…Fractures of the distal end of the clavicle account for 10% -30% of all fractures of this bone, and are the second most common fractures, after diaphyseal fractures [1][2][3]. At the same time, they have the greatest frequency of non-unions and malunions -as many as 50% [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…Fractures of the distal end of the clavicle account for 10% -30% of all fractures of this bone, and are the second most common fractures, after diaphyseal fractures [1][2][3]. At the same time, they have the greatest frequency of non-unions and malunions -as many as 50% [1,4]. Neer type IIB fractures are defined as fractures in the region of the coracoclavicular (CC) ligament wherein the conoid segment of the CC ligament is disrupted and there is a dislocation of the proximal fragment [1,5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations